What Are the Data Privacy Concerns with AI Medical Imaging? - Rasit, Dinc (Rasit Dinc Digital Health & AI Research, 2020)
The integration of artificial intelligence (AI) into medical imaging has ushered in a new era of diagnostic capabilities, promising to enhance the accuracy a...
Keywords: AI in Medical Imaging and Diagnostics; Privacy; Concerns; Medical; Artificial Intelligence; Healthcare; Medical Imaging